Cognitive architecture: The key to aI-based digital transformation in organizations - Olmos Sanchez, Karla Miroslava (IOS Press, 2018)
The objective of this paper is to present a framework of work for organizations to became cognitive systems through the KMoS-RE systematic knowledge management process. A summary of the application of the framework in a freight company is presented. Promising results provide evidence of the usefulness of the framework in the era of AI-based digital transformation